Penentuan Interval Waktu Pemeliharaan Pencegahan pada Peralatan Sub-Unit RKC 3 di PTX Pabrik Tuban - Fesa Putra Kristianto; Bobby O.P. Soepangkat (UNUSA Press, 2017)
PT X Tuban Plant has four plants (unit), namely Tuban I, Tuban II, Tuban III and Tuban IV. Each unit plant has three sub units, i.e., Crusher Operations Sub-Unit, Raw Mill, Kiln and Coal Mill (RKC) Sub-Unit and Finish Mill Sub-Unit. RKC 3 Sub-Unit in Tuban III has the highest number of equipment downtime and production loss. Therefore, it was necessary to optimize the time interval of preventive maintenance ( ) and total labor force as part of the company maintenance policy, would also fulfill the required reliability and availability of RKC 3 Sub-Unit. There were two steps in determining Tp optimum. The first step was to obtain the best distribution of the time between failures (TBF) and time to repair (TTR). The next step was to iterate the operating time (Ti) and Tp to determine the minimum preventive maintenance cost rate, reliability and maintainability.This iteration was applied to sub-units of RKC 3 that possesses a series system. Tp at the lowest rate of maintenance costs was the optimum Tp. The optimum Tp for RKC 3 Sub-Unit is 3743,28 hour. The preventive maintenance cost rate for optimum Tp is Rp33.100/hour and the reliability and availability of sub unit are 96,7% and 99,86% respectively.Keywords: reliability, availability, preventive maintenance cost rate, and preventive maintenance